Climate-driven distribution shifts of Iranian amphibians and identification of refugia and hotspots for effective conservation - Somaye Vaissi; Alireza Mohammadi (Scientific Reports)
Abstract This study investigates the potential impacts of climate change on the distribution of Iranian amphibian species and identifies refugia and biodiversity hotspots to inform effective conservation strategies. The study employed ensemble species distribution models to assess the impacts of climate change on 19 Iranian amphibian species. We analyzed future scenarios (2041–2060 & 2081–2100) under a high-emission pathway to identify potential range shifts and refugia (areas with stable or newly suitable climate). Additionally, core habitat overlays were used to map amphibian diversity hotspots and evaluate their coverage within existing protected areas. Climate change is projected to threaten the habitat of most Iranian amphibian species, with potential for some species to expand into new areas. The study differentiates in-situ and potential ex-situ refugia under worst-case climate models (GISS-E2-1-G and MRI-ESM2-0). GISS-E2-1-G suggests expansive refugia encompassing the Hyrcanian forests, Alborz, Zagros, and Kopet Dag mountains, along with the southern coast. MRI-ESM2-0 indicates more restricted refugia in these regions. Importantly, there is an overlap between climatic refugia and existing biodiversity hotspots. However, the overlap between amphibian hotspots and protected areas is currently 7.41%, projected to decrease to 5.30–5.51% by 2081–2100 under both models. This research emphasizes the significance of areas serving as both refugia and biodiversity hotspots for amphibian adaptation and long-term survival. The study proposes a dynamic conservation approach that necessitates continuous assessments and adaptable management strategies to ensure effectiveness in a changing climate.